Employee Engagement in Higher Education: Financial impact of engagement in higher education (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
Employee engagement is a critical issue across many industries, none more critical than in higher education. The examination herein is focused on the financial impact faculty/staff engagement can have on the higher education enterprise and beyond.